Potencjał dynamicznej platformy webtoons.com/fr w nauczaniu/uczeniu się języka francuskiego w opinii studentów filologii romańskiej - Chmiel-Bożek, Halina (Neofilolog, 2024)
Reading is an important element of independent work on the language, but offering students additional reading to improve their linguistic and cultural competences is an extremely difficult task, due to the evolving tastes of young people and the variability of the media they use. Given the popularity of manga and digital comics in France, Romance philology students were asked to read a series selected from the webtoons.com/fr platform in French. A survey was then carried out to find out their views on how this tool could be used in French language learning. The results of the survey clearly indicate that the webtoons.com/fr platform can be used as an effective tool for learning French. According to the respondents, reading the selected series allowed them, above all, to develop lexical resources and was also an enjoyable pastime that increased motivation to learn the language. Students also paid attention to the combination of word and image, appreciating both the aesthetic and practical side of reading digital comics. Finally, the practicality of using the platform, its ease of use and accessibility was emphasised.